2016
DOI: 10.1117/1.jmi.3.4.046002
|View full text |Cite
|
Sign up to set email alerts
|

Postediting prostate magnetic resonance imaging segmentation consistency and operator time using manual and computer-assisted segmentation: multiobserver study

Abstract: Prostate segmentation on T2w MRI is important for several diagnostic and therapeutic procedures for prostate cancer. Manual segmentation is time-consuming, labor-intensive, and subject to high interobserver variability. This study investigated the suitability of computer-assisted segmentation algorithms for clinical translation, based on measurements of interoperator variability and measurements of the editing time required to yield clinically acceptable segmentations. A multioperator pilot study was performed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…The average operator interaction time was 27 s. per subject. The total segmentation time including the operator interaction time was about one min per 3D image which is substantially less than fully manual segmentation time reported in the literature (i.e., about 5 to 20 minutes per 3D image) [6,19,35].…”
Section: Segmentation Algorithm Accuracy and Computation Timementioning
confidence: 68%
See 3 more Smart Citations
“…The average operator interaction time was 27 s. per subject. The total segmentation time including the operator interaction time was about one min per 3D image which is substantially less than fully manual segmentation time reported in the literature (i.e., about 5 to 20 minutes per 3D image) [6,19,35].…”
Section: Segmentation Algorithm Accuracy and Computation Timementioning
confidence: 68%
“…Contouring of the prostate gland on T2-weighted MR images could assist with MRI-guided procedures used for PCa diagnosis and management [4]. However, manual delineation of the prostate border is a time-consuming task with high inter-observer variability [5,6]. One solution to address these issues is to use computer-assisted segmentation algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, an observer study is required to confirm the effectiveness of this approach for prostate segmentation in a real clinical situation. In addition, although our previous studies 13,14,17 showed that using minimal user interaction for prostate segmentation could substantially speed up the process when compared to manual segmentation time, the observer study must confirm that for this study.…”
Section: Limitationsmentioning
confidence: 72%